Denetçi Rol ve Yeterlikleri Bağlamında 1999, 2011 ve 2014 Müfettişlik YönetmeliklerininMüfettiş Yardımcısı Atama ve Yetiştirme Anlayışlarının Karşılaştırılması - Turan Akman Erkılıç; Engin Dilbaz (Anı Publishing, 2015)
The purpose of this study is to compare the dimensions of the appointment requirements for assistant inspectorship, competitive examination and inspector training in the inspectorship regulations dated 1999, 2011 and 2014 in the context of supervisor roles and adequacies. The study is a content analyzing type of research. These three regulations of the subject of the research is evaluated in the context of supervisor roles and qualifications then, analyzed by the help of qualitative content analyzing method. The findings are considered within the framework of categories in line with the research purpose. In conclusion, the dominance of the conception of centralized management and bureucratic process are observed. Besides this, when the rate of change in the 21st century taken into account, the roles of supervisors have becomevaried and an expansion in qualification areas comes into question. Accordingly, It is seen that the regulations show more functional and integrative qualifications, and show a globalization and neo-liberal change tendency from former to latter. Besides the partial change seen in the regulations in terms of supervisor roles and qualifications; it is seen that the content is predominantly prepared through fulfilling the socio-economic and political necessities.